The modified Glasgow prognostic score (MGPS) and the mortality prediction model II (MPM II) can predict mortality in patients with breast cancer admitted to intensive care: A retrospective cohort study: Inflammation markers in breast cancer patients in intensive care - Tunay, Burcu; Olmez, Omer Fatih; Bilici, Ahmet; Bayramgil, Ayberk; Cavusoglu, Gunes Dorukhan; Oz, Huseyin (Journal of Surgery and Medicine, 2023)
Background/Aim: Breast cancer is the second most common cause of cancer-related death in women worldwide. Predicting the prognosis in breast cancer with very high mortality is important in terms of disease treatment and increasing life expectancy. In our study, we aimed to examine the importance of some inflammatory markers and scoring systems in predicting prognosis in patients with breast cancer who were hospitalized in the intensive care unit. Methods: This retrospective cohort study was conducted in the Department of Medical Oncology and Intensive Care Unit between 2014 and 2020. Breast cancer patients who were admitted to the intensive care unit at any stage of their treatment during the study and followed up and treated in the medical oncology department of the hospital were included in the study. All data were compared between groups (discharged or exitus) based on survival status. Socio-demographic information, laboratory findings (hemoglobin, leukocytes, neutrophils, lymphocytes, platelets, eosinophils, monocytes, C-reactive protein [CRP], albumin, lactate dehydrogenase [LDH], clinical status [co-morbidities, length of stay in intensive care, mechanical ventilation, and reason for hospitalization in the intensive care unit]), and survival data of the patients were collected retrospectively from hospital medical records. We also recorded treatment-related data and relapse/progression information. Neutrophil–lymphocyte, platelet–lymphocyte, and lymphocyte–monocyte ratios (NLR, PLR, and LMR, respectively) were calculated. Results: Thirty-seven (52.1%) patients died and 34 (47.9%) patients survived. The NLR (P=0.021), Modified Glasgow Prognostic score (P<0.001), APACHE II score (P<0.001) and mortality probability model (MPM II) upon admission (P<0.001) were significantly higher in the exitus group than in the survivors. The lymphocyte_monocyte ratio (P=0.030) and prognostic nutritional index (P=0.004) were significantly higher in the discharged group than in the death group. When we evaluated performance of the prognostic scores to predict mortality, we found that the APACHE II score (area under the curve [AUC]: 0.939, 95% confidence interval [CI]: 0.888–0.990), MPM II-Admission (AUC: 0.936, 95% CI: 0.880–0.992), and modified Glasgow Prognostic Score ([mGPS] AUC: 0.727, 95% CI: 0.600–0.854) had the highest area under curve values. Multivariable regression revealed that longer chemotherapy duration (≥2 weeks), an mGPS score of two points, and high MPM-II (≥36 points) were independently associated with mortality. Conclusion: Among the inflammatory markers and scores examined, mGPS and MPM-II were found to be independently associated with mortality in breast cancer patients who were hospitalized in the intensive care unit. In addition, patients with longer chemotherapy duration had a higher risk of mortality, but this result was limited by various possible confounders.